2010
DOI: 10.1055/s-0030-1248103
|View full text |Cite
|
Sign up to set email alerts
|

Proximity of the Popliteal Artery to the PCL During Simulated Knee Arthroscopy – Implications for Establishing the Posterior Trans-Septal Portal

Abstract: This study defi nes the sagittal distance from the posterior cruciate ligament (PCL) to the popliteal artery under simulated arthroscopic conditions. This information is relevant for posterior knee arthroscopy, particularly for the safe establishment of the posterior trans-septal portal. Measurements from the PCL to the popliteal artery were made on sagittal magnetic resonance images obtained in a previous study of 10 fresh-frozen cadaveric knees. The mean sagittal distance from the mid-PCL to the popliteal ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…One of the critical issues of concern regarding the posteromedial aspect is injury to the saphenous nerve and vessels. 14 In this study we propose an inside-out technique to create a direct posterior portal in the knee. The benefit of this technique is the avoidance of injury to the saphenous nerve, as well as the popliteal vessel, using transillumination.…”
mentioning
confidence: 99%
“…One of the critical issues of concern regarding the posteromedial aspect is injury to the saphenous nerve and vessels. 14 In this study we propose an inside-out technique to create a direct posterior portal in the knee. The benefit of this technique is the avoidance of injury to the saphenous nerve, as well as the popliteal vessel, using transillumination.…”
mentioning
confidence: 99%
“…mean sagittal distance from the mid-PCL to the popliteal artery to be 29 mm (range, 18-55 mm). 11 This distance decreased to 10 mm (range, 3-16 mm) at the PCL insertion on the tibia. 11 Thus, the posterior septum can be safely divided at its center (at the level of the mid-PCL) to create a transseptal portal that permits access between the posteromedial and posterolateral compartments, as described below.…”
Section: A 4bmentioning
confidence: 88%
“…11 This distance decreased to 10 mm (range, 3-16 mm) at the PCL insertion on the tibia. 11 Thus, the posterior septum can be safely divided at its center (at the level of the mid-PCL) to create a transseptal portal that permits access between the posteromedial and posterolateral compartments, as described below. 2 The knee flexion angle also affects popliteal artery position.…”
Section: A 4bmentioning
confidence: 88%
“…Creating the tibial tunnel in PCL surgery is 1 of the most technically demanding portions of transtibial PCL recon- 1 n sports medicine update struction due to the proximity of neurovascular structures to the PCL insertion. 12,13 In a cadaveric study during simulated arthroscopic conditions, Cosgarea et al 12 found the mean sagittal distance of the politeal artery to the mid-PCL was 29.1 mm and to the proximal PCL fovea was 9.7 mm. The distance between the PCL insertion and popliteal artery varies depending on the degree of knee flexion.…”
Section: Tibial Tunnelmentioning
confidence: 99%